THE EFFECTIVENESS OF SOCIAL MEDIA IN SUPPORTING THE PUBLIC RELATIONS ROLE OF THE INDONESIAN ULEMA COUNCIL IN BUILDING ORGANIZATIONAL IMAGE AND CREDIBILITY - Dwi Asyila Sabrina Br. Saragih; Sri Indah Wati Haraha; Muammar Dzaki Ihsan; Muqtada Ibrahim (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines the public relations role of the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) in building the organization's image and credibility through social media. Employing a qualitative approach with a case study method and social media content analysis, the findings reveal that MUI has actively utilized various social media platforms to disseminate religious information, fatwas, and relevant programs, contributing to increased public engagement. Social media has proven effective in shaping MUI's image and credibility, particularly in raising public awareness and trust in the organization. The study recommends that MUI continue to strengthen its social media strategy to build organizational image and credibility, as well as to regularly monitor and analyze the effectiveness of its social media efforts. This research provides significant implications for MUI in leveraging social media to enhance its image and organizational credibility.